2018
DOI: 10.2217/fon-2018-0087
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline Phosphatase in Metastatic Castration-Resistant Prostate Cancer: Reassessment of an Older Biomarker

Abstract: Since most patients with metastatic castration-resistant prostate cancer (mCRPC) have bone metastases, it is important to understand the potential impact of therapies on prognostic biomarkers, such as ALP. Clinical studies involving mCRPC life-prolonging agents (i.e., sipuleucel-T, abiraterone, enzalutamide, docetaxel, cabazitaxel, and radium-223) have shown that baseline ALP level is prognostic for overall survival, and may be a better prognostic marker for overall survival than prostate-specific antigen in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 94 publications
1
43
0
Order By: Relevance
“…Data coming from literature have shown that baseline tALP level is prognostic for OS. 28 Anyway, an increased risk of death, time to progression, skeletal-related events, and bone marrow failure are possibly related to pre-treatment tALP levels (≥146 U/L): this admits to hypothesize a predicting role for this marker. 29 In addition to that, from a retrospective analysis of data from the ALSYMPCA trial emerged that patients treated with Ra-223 and with confirmed decline in tALP at week 12 had a significantly longer OS.…”
Section: Discussionmentioning
confidence: 99%
“…Data coming from literature have shown that baseline tALP level is prognostic for OS. 28 Anyway, an increased risk of death, time to progression, skeletal-related events, and bone marrow failure are possibly related to pre-treatment tALP levels (≥146 U/L): this admits to hypothesize a predicting role for this marker. 29 In addition to that, from a retrospective analysis of data from the ALSYMPCA trial emerged that patients treated with Ra-223 and with confirmed decline in tALP at week 12 had a significantly longer OS.…”
Section: Discussionmentioning
confidence: 99%
“…Since 90% of the mCRPC patients have radiologic evidence of bone metastasis [3], alkaline phosphatase is an important biomarker in prostate cancer. For cabazitaxel, no direct effect on alkaline phosphatase is known, only indirect when the tumor burden decreases, alkaline phosphatase levels also decrease [19]. Also for hemoglobin no direct effect of cabazitaxel is known.…”
Section: Discussionmentioning
confidence: 99%
“…Differentiation of hMSCs to osteoblastic lineages in vitro is associated with their ability to express Col I and ALP. Col I is expressed by osteoblasts during the initial period of proliferation and ECM synthesis, while ALP is expressed during the post proliferative period of matrix maturation [260,261,262,263]. Osteogenic differentiation of hMSCs in vitro is greatly enhanced by DEXA.…”
Section: In Vitro Studiesmentioning
confidence: 99%